Creeping Bentgrass Putting Green Response to Combined Mowing, Rolling, and Foot Traffic Under Environmental Stress. (1st November 2015) - Young, Joseph; Richardson, Mike; Karcher, Doug
Abstract : Creeping bentgrass ( Agrostis stolonifera L.) putting greens in the transition zone experience high levels of environmental stress during summer months. The interaction of common management practices combined with foot traffic can exacerbate environmental stress. The objective of this study was to determine the effect of management practices combined with foot traffic during high environmental stress in the transition zone. Creeping bentgrass cultivars, SR 1020 and Penn G2, were managed with various mowing heights (2.5, 3.2, or 4.0 mm), rolling frequencies (0, 3, or 6 d per week), and foot traffic. As environmental stress became prominent during summer months, bentgrass maintained at the lowest mowing heights exhibited poorer turf quality, coverage, and wear tolerance compared to the highest mowing height. SR 1020 quality was reduced below acceptable levels in July when mowed at the lowest mowing height in 2011 and 2012. Penn G2 maintained acceptable quality at all mowing heights in 2011, but severe heat and drought stress reduced turf quality regardless of mowing height in 2012. Daily rolling significantly increased wear on both cultivars during high environmental stress that resulted in decreased turf quality and coverage compared to the non‐rolled treatments. The combination of wear from mechanical stress and foot traffic increased wear injury on both cultivars. Under reduced daylengths and optimal air temperatures in September of each year, all response variables improved to similar levels.